Characterization and expression profiling of PIN auxin efflux transporters reveal their role in developmental and abiotic stress conditions in rice - Manna, Mrinalini; Rengasamy, Balakrishnan; Ambasht, Navin Kumar; Sinha, Alok Krishna (Frontiers in Plant Science, 2022)
The auxin efflux transporter proteins called PINs ferry auxin from its source to sinks in particular directions depending on their polar localizations in the plasma membrane, thus facilitating the development of the entire plant architecture. The rice genome has 12 PIN genes distributed over eight chromosomes. To study their roles in plant development, abiotic stress responsiveness, and shaping an auxin-dependent root architecture, a genome-wide analysis was carried out. Based on phylogeny, cellular localization, and hydrophilic loop domain size, the PINs were categorized into canonical and noncanonical PINs. PINs were found expressed in all of the organs of plants that emphasized their indispensable role throughout the plant’s life cycle. We discovered that PIN5C and PIN9 were upregulated during salt and drought stress. We also found that regardless of its cellular level, auxin functioned as a molecular switch to turn on auxin biosynthesis genes. On the contrary, although PIN expression was upregulated upon initial treatment with auxin, prolonged auxin treatment not only led to their downregulation but also led to the development of auxin-dependent altered root formation in rice. Our study paves the way for developing stress-tolerant rice and plants with a desirable root architecture by genetic engineering.